Accidental injury of the latissimus dorsi flap pedicle during axillae dissection: Types and reconstruction algorithm. Issue 1 (9th July 2013) - Laporta, Rosaria; Longo, Benedetto; Pagnoni, Marco; Catta, Federico; Garbarino, Giovanni Maria; Santanelli, Fabio
<x xml:space="preserve">Abstract</x> The intra‐operative latissimus dorsi (LD) pedicle damage during axillary lymph‐node dissection by the general surgeon is a rare complication leading to flap failure and poor outcomes. The authors present their experience on this topic and develop a classification of the thoracodorsal (TD) pedicle injuries and reconstruction algorithm. Pedicle damage of LD occurred in five cases, three of which were experienced during immediate breast reconstruction and two observed in patients who underwent prior surgery. In two cases the thoracodorsal vein (TDV) was damaged in its proximal segment, thus end‐to‐end anastomosis was performed between distal stump of TDV and circumflex scapular vein (CSV). In one case the TDV required simple microsurgical repair while in other two cases the severe damage of vein and artery required more complex surgical strategies in attempt to salvage the flap. Four cases completely survived with one case of rippling phenomenon. One case had partial flap necrosis that required subtotal muscle resection. Based on these cases, the authors have developed a reconstruction algorithm in attempt to repair LD pedicle damage while preserving breast reconstruction. Taking into account its anatomical conformation, TD pedicle injuries are classified in four different types and available options are suggested for all of them according to the anatomical site and to the mechanism and timing of injury. © 2013 Wiley Periodicals, Inc. Microsurgery 34:5–9, 2014.